PROPOSED MARKETING STRATEGY FOR KOFLUCK COFFEE SHOP - DANA FATMA (NIM: 29114378), ANGGER
Kofluck is a coffee shop that has been established since 2010 in Bandung. Kofluck owns a coffee plantation in Ciwidey area that produces Arabica type coffee, Gayo, Toraja Pulu-Pulu Bajawa, Mandailing, and Bali Kintamani. The plantation is a supplier of coffee beans for Kofluck. Since the founding of Kofluck in 2010 until 2014, Kofluck posted a 40% revenue increase per year. However, until 2016, Kofluck's revenue continued to decline. This is allegedly because of marketing efforts that are not optimal. Without any changes, it is feared Kofluck can not survive in this industry. Based on those facts, Kofluck should create new strategy to increase sales and find ways to pursue and maintain their target market. Internal and external analysis is done to find out the root of the problem that occurred in Kofluck. Based on the results of the analysis is known that the cause of sales decline due to competition coffee shop is increasingly tight in Bandung. Kofluck has difficulty competing with his competitors because Kofluck does not have a clear marketing strategy especially in its target market, food and beverage limitations, low promotions, and unattractive processes. Therefore, Kofluck requires a new strategy that aims to increase Kofluck's sales in the future and survive in this industry. Kofluck has four strategic options to address the previously described problems of formulating new promotional strategies, multiplying product choices (food and beverage), creating membership programs, and making customer experience appealing to consumers. Nevertheless, from the whole choice of strategy, Kofluck must first determine their target market so that the target consumer desire more can be fulfilled. There are 2 potential segments in coffee shop industry which are coffeeholic and common guest. Based on cluster analysis, coffeeholic is considered a potential target of Kofluck consumers because based on the results of the questionnaire has the most number. Based on these results, a newly created marketing mix focuses on product, process, and promotion which suitable with coffeeholic`s preferences that use cross tabulation tools. In the product, the strategy that needs to be applied is to add food and drink menu variants but not to release the image of coffee. In the process, the strategy that needs to be applied is to create a new process where consumers can use their own coffee machine, see the action of barista, live music, and application of Juke Box. In promotion, the strategy that needs to be implemented is to optimize the use of social media by increasing engagement so that campaigns can be optimized with a more minimal cost. There are several steps that Kofluck needs to take in executing these strategies: food and beverage research, searching for additional suppliers, preparing social media related content and admin for promotion, redesigning the interior, preparing SOPs for baristas, cooks and cashiers, training employees to be able to guide consumers in operating the coffee maker, preparing the Juke Box and its playlists, and preparing the infrastructure for live music. For the preparation phase alone it will take 3-4 months and this strategy will run for one year which then must be evaluated every year.